(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
India has been progressively promoting cashless transactions as part of its monetary policy, aiming to reduce the dependency on cash and promote digital payments. This shift has implications for small and medium-sized enterprises (SMEs) in the country. This study delves into the ramifications of India's transition towards a cashless monetary policy, specifically examining its impact on Small and Medium-Sized Enterprises (SMEs). As India endeavours to embrace digital transactions and reduce reliance on cash, this shift poses unique challenges and opportunities for SMEs, which form the backbone of the nation's economy. The research aims to unravel the multifaceted effects on SMEs, encompassing aspects such as operational efficiency, financial inclusion, and adaptability to technological changes. By scrutinizing the intricacies of this policy transformation, the study endeavours to provide valuable insights for policymakers, business owners, and stakeholders alike, contributing to a nuanced understanding of the broader economic landscape.